Guidelines for developing quality of life for the elderly: A community-based approach - Pattrawiwat, Kanchana; Charuchinda, Arthitaya; Numkanisorn, Phiranant; Suvarnasara, Chainarong; Peltzer, Karl (Humanities, Arts and Social Sciences Studies, 2022)
This research aimed to study and develop guidelines to improve the quality of the lives of the elderly in the Posa Subdistrict of the Angthong Province in Thailand. The study was divided into three steps: step one was to evaluate the quality of life and to survey the needs of the elderly, step two was to study the prototype of a life quality plan for the elderly, and step three was to establish guideline development for the quality of life of the elderly using community-based participatory research and the AIC technique. The study participants consisted of 171 elderly people in the Posa Subdistrict, seven administrators and 15 members of the elderly center prototype in Phang Nga Province, and 14 elderly people, a mayor, a vice- mayor, two city council members, and four public health volunteers in the Posa Subdistrict. The study was conducted using frequencies, percentage and inductive analysis for data analysis. The study concluded the following as guidelines to develop quality of life for the elderly: (1) in the physical domain, the community should provide training for the elderly and their caregivers in the field of health care; (2) in the psychological domain, the promotion of the values of the elderly and family-based care for the elderly should be encouraged; (3) in the social relationships domain, the community should establish a center for the elderly, to encourage and support them to participate in social activities; and (4) in the environmental domain, the establishment of volunteer caretakers for the elderly in the village should be initiated, and a care surveillance unit to provide safety and convenience for elderly should be set up. This research offers some recommendations and that family and community-based care has the potential to develop quality of life among the elderly in the psychological domain, which is a fundamentally better quality of life in other aspects of the elderly.